Comparing Organic Paddy Farming Continuance Intention Across Farmers’ Attributes Using a Non-Parametric Approach - Azizatun Nurhayati; Nolila Mohd Nawi; Nitty Hirawaty Kamarulzaman; Ahmad Hanis Izani Abdul Hadi; Irham Irham (Caraka Tani: Journal of Sustainable Agriculture, 2026)
The adoption stage is not the end of the diffusion of organic paddy farming. To ensure long-term engagement, continuance intention must be assessed during the post-adoption stage. This study aims to investigate the status of continuance intention and evaluate score variance across 14 farmers’ attributes. The research involved 345 organic paddy farmers in Magelang, Central Java, Indonesia. A 5-point Likert-scale questionnaire was administered to assess the respondents’ continuance intention. Non-parametric tests, namely the Kruskal-Wallis and Mann-Whitney tests, were performed to examine differences in the mean ranks of the continuance intention composite scores across attribute groups. The results showed that the majority of organic farmers (66.08%) possess high continuance intention. The differences in mean ranks of continuance intention score were also revealed across the groups of ‘role in farmer groups’, ‘renewal of organic certification status’, ‘farm ownership’, ‘organic paddy farming experience’, and ‘the frequency of organic certification renewal’. In addition, the mean rank score of continuance intention for ‘renters’ was significantly higher than that of ‘landowners’. These findings suggest that farmers’ attributes could be incorporated into the consideration of an actionable plan to preserve and enhance farmers’ intentions.